Effect of interface morphology on tensile response of Ti6Al4V alloy fabricated by laser hybrid additive manufacturing: Experiments & simulations - Wei Fan; Guang Hu; Yuguang Chen; Yue Du; Yijie Peng; Yongxia Wang; Yunlong Li; Hua Tan; Fengying Zhang; Xin Lin (Journal of Materials Research and Technology)
Hybrid manufacturing, which integrates forging and directed energy deposition (DED), offers transformative potential for fabricating large, complex titanium alloy components. Despite its promise, the inherent disparity in microstructures between the wrought substrate and DED part introduces cross-regional mechanical heterogeneity, limiting structural reliability. This study established a model to investigate the mechanical response of hybrid-manufactured Ti6Al4V with flat and curved interfaces. The model incorporates anisotropic properties of the DED part and accounts for multi-scale microstructural variations across regions. A novel numerical simulation approach is employed to capture the transitional properties of the interface, which are often simplified in traditional models. Experimental validation and finite element analysis (FEA) are combined to explore the impact of interface geometry on stress distribution and load transfer mechanisms. The evolution of stress fields under tensile loading was compared for flat and curved interfaces, revealing that stress concentration factors remain below 1.05 even under large strain conditions. However, curved interfaces exacerbate stress concentration in the central wrought substrate, elevating stress peaks at the distal end of the interface. This effect, driven by altered load transfer pathways, increases strain gradients and the risk of premature failure in the substrate. While ultimate tensile strengths for flat and curved interface specimens are comparable, the elongation of curved interfaces is reduced by approximately 10%. The findings provide a framework for optimizing interface design to improve mechanical performance, offering insights for future advancements in additive manufacturing of components with inhomogeneous microstructure.